A Novel Configuration of a Reconfigurable Planar BandPass Filter For Wireless Power Transfer - El Maimouni Soufiane; Aytouna Fouad; Zbitou Jamal; Gibarii Mohammed El; Samira Khoulji; Elabdellaoui Larbi (EPJ Web of Conferences)
This paper presents the design and analysis of a novel microstrip bandpass filter (BPF) using square split ring resonators (SRRs) as resonating elements. The proposed filter architecture comprises a modified microstrip line section coupled to microstrip lines on either side, with an integrated SRR positioned centrally. The SRR elements are strategically designed and optimized to achieve the desired frequency response. The filter is fabricated on an FR-4 substrate with a thickness of 1.6 mm, a dielectric constant of 4.4, and a loss tangent of 0.025. It features a compact size of 9x26.3mm².This study will initially present the simulation results of the designed filter. Subsequently, the filter will be transformed into a tuneable configuration. one approache will be investigated a reconfigurable structure where the variable capacitance is varied to adjust the bandwidth while maintaining the filter's physical dimensions, The integration of capacitance enables dynamic tuning capabilities for the bandpass filter. This design represents a significant advancement in filter technology, with promising applications in next-generation communication systems that require high levels of flexibility and performance. This filter is designed for wireless power transmission and is compatible with applications operating in the vicinity of 2.4GHz to 2.5GHz.